Belajar Tanpa Batas: Pelatihan Learning Management System sebagai Kunci Inovasi Edukasi Digital - Hayati, Rahmi; M Rezeki Muamar; Hakim Muttaqim; Fachrurazi; Asrul Karim (PELITA NUSA TENGGARA, 2025)
The transformation of higher education in the digital era requires lecturers to have the competence to utilize learning technology effectively, including the utilization of Learning Management System (LMS). However, many lecturers have not optimized LMS as an interactive and structured learning tool. This Community Service Program aims to improve lecturers' ability to use LMS through technical and pedagogical training based on direct practice and andragogical approaches. Activities are carried out through preparation stages, three-day intensive training, two-week implementation assistance, and evaluation. The results show a significant increase in lecturers' competence in managing LMS, with an average score increasing by 32 points after training. Active participation of partners, the success of the digital class mini project, and the formation of an LMS practitioner community are positive indicators of the program's success. Outputs in the form of modules, video tutorials, and digital learning products make a real contribution to improving the quality of online learning in the higher education environment. This program has the potential to be widely and sustainably replicated to support inclusive and adaptive digitalization of education.